A REVIEW ON TOXICITY OF CALOTROPIS (ARKA) AND MANAGEMENT - Mahesh Hadimani, Seema; M. G, Anitha (International Journal of Ayurveda and Pharma Research, 2015)
The herbal medicine occupies distinct position right from ancient period in Ayurveda. Arka (Calotropis) an important drug of Ayurvedic toxicology and therapeutics is known in India from ancient period since Samhitakala. There are two types of Arka mentioned in Ayurveda. Sweata arka (Calotropis gigantea) and Rakta arka (Calotropis procera). Among the two Raktaarka (Calotropis procera) is more toxic and is assumed even more poisonous than cobra venom. Both these plants belong to Asclepiadaceae family and closely resemble each other in chemical and physiological actions. It is included under Bhedaniya (Vagbhata) Vamanopaga, Svedopaga (Caraka), Arkadi, Adhobhagahara, gana (Susruta) and also included under Guduchyadi Osadhi varga. Toxic principals are Uscharin, Calotoxin, Calactin, Calotropin, Calotropage. Ksheera (Milk) being an irritant, neurotoxic and also due to anticholinergic responses cause toxicity and various fatal presentation. Serum containing 3% of Gigantin is highly virulent CSF toxicant. Toxic symptoms are Vanti (vomiting), Rechana (diarrhoea) on ingestion. It exerts caustic (Kshara) effect to the skin on direct contact. It can lead to blindness if its latex is put in to the eyes, causing opacity to the cornea. Ghee is considered to be an antidote for internal usage and external application of Cincha patra kalka. The dried latex and dried root are used as an antidote for snake poisoning in Bagata tribe of Eastern Ghats of Visakhapatnam district, Andhra Pradesh. A detailed account of toxic effect of Arka and its descriptions in Ayurveda along with its management have been emphasized in the present review with toxic symptoms, management, medico legal cases and case reports.